Pengaruh Media Sosial Instagram @Jampoundbic Terhadap Pentingnya Minat Olahraga - Muhammad Revansyaych; Ari Suseno; Yoman, Mad (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
This study investigates t\he impact of the Instagram social media platform, specifically the account @jampoundbic, on the public's interest in exercise, particularly Poundfit. In today's digital age, social media plays a crucial role in transforming how people communicate and interact. The primary issue addressed is how social media can motivate individuals to engage in exercise, especially in the context of the trending Poundfit activity. The aim is to measure the extent of the influence of the Instagram account @jampoundbic on shaping sports interest among the residents of Tangerang, particularly in Bumi Indah City. The research employs a quantitative method with a positivist approach, involving data collection from 100 respondents aged 20 to 40, consisting of 3 males and 97 females. The findings indicate that Instagram has a significant impact on sports interest, with a coefficient of determination reaching 52.5%. Regression analysis shows a positive relationship between Instagram usage and increased sports interest. The study concludes that social media can be an effective tool for promoting exercise and enhancing community participation in sports.